Isolated atrial amyloidosis suspected by electrophysiological voltage mapping and diagnosed by 99mTc‐DPD scintigraphy. (4th October 2020) - Doreen, Schöppenthau; Imke, Schatka; Alexander, Berger; Burkert, Pieske; Hahn, Kathrin; Fabian, Knebel; Felix, Kleefeld; Alexander, Tobias; Jin‐Hong, Gerds‐Li; Daniel, Messroghli
Abstract: We present not‐yet‐seen multimodal images of a 55‐year‐old female patient with isolated atrial amyloidosis (IAA) who clinically suffered from multiple atrial arrhythmias and heart failure symptoms with preserved left ventricular ejection fraction. We aim to show structural and functional abnormalities detected by electrophysiological voltage mapping, cardiac magnetic resonance imaging (MRI) [cMRI; atrial strain measurements, late gadolinium enhancement (LGE) visualization], and 99m Tc‐DPD scintigraphy. Bipolar voltage mapping performed during two electrophysiological procedures showed diffuse left atrial low‐voltage areas (bipolar < 0.5 mV) and also a moderately diseased right atrium suspected of infiltrative cardiomyopathy. Catheter ablation did successfully treat a left atrial and two right atrial focal tachycardias. For further diagnostics, a 3T cMRI was performed, revealing a subendocardial circumferential left atrial LGE and pathological atrial strain measurements, especially during conduit and reservoir phase. Afterwards, nuclear imaging with 559 MBq of 99m Tc‐DPD was performed. The scan revealed amyloid infiltration of the left atrium. Neither an uptake in the ventricular myocardium nor an extra‐cardiac uptake of DPD was seen. Genetic testing for transthyretin amyloidosis mutations in this patient was negative, and peripheral neuropathy was ruled out by electromyogram analysis. The synopsis of these findings reveals IAA as the most possible diagnosis and showed isolated atrial nuclear tracer uptake with 99m Tc‐DPD scintigraphy for the first time. Non‐invasive imaging techniques might help in suggesting IAA but need further investigation.